EDUKASI TENTANG PENERAPAN PROTOKOL KESEHATAN DALAM UPAYA PENCEGAHAN COVID-19 - Irmayani Irmayani; Sri Melda Bangun; Anggi Isnani Parinduri; Raisha Octavariny (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
The end of 2019 to be precise in December, the world community was shocked by the corona virus. The increasing number of cases which is increasing in such a fast time has caused COVID-19 to become a pandemic. This paper aims to provide education on the application of health protocols in efforts to prevent COVID-19 in Serdang Bedagai Regency, North Sumatra Province. The method of implementing this activity is through observation and providing health education on the application of health protocols in efforts to prevent COVID-19 to the public. From the results of the activities carried out, the community enthusiastically welcomed this activity. It is hoped that with this activity, people's behavior in implementing health protocols will increase.